Efficient derivation of functional astrocytes from human induced pluripotent stem cells (hiPSCs) - Szeky, Balazs; Jurakova, Veronika; Fouskova, Eliska; Feher, Anita; Zana, Melinda; Karl, Vivien Reka; Farkas, Janos; Bodi-Jakus, Maria; Zapletalova, Martina; Pandey, Shashank; Kucera, Radek; Lochman, Jan; et al. (PloS one, 2024)
Astrocytes are specialized glial cell types of the central nervous system (CNS) with remarkably high abundance, morphological and functional diversity. Astrocytes maintain neural metabolic support, synapse regulation, blood-brain barrier integrity and immunological homeostasis through intricate interactions with other cells, including neurons, microglia, pericytes and lymphocytes. Due to their extensive intercellular crosstalks, astrocytes are also implicated in the pathogenesis of CNS disorders, such as ALS (amyotrophic lateral sclerosis), Parkinson's disease and Alzheimer's disease. Despite the critical importance of astrocytes in neurodegeneration and neuroinflammation are recognized, the lack of suitable in vitro systems limits their availability for modeling human brain pathologies. Here, we report the time-efficient, reproducible generation of astrocytes from human induced pluripotent stem cells (hiPSCs). Our hiPSC-derived astrocytes expressed characteristic astrocyte markers, such as GFAP, S100b, ALDH1L1 and AQP4. Furthermore, hiPSC-derived astrocytes displayed spontaneous calcium transients and responded to inflammatory stimuli by the secretion of type A1 and type A2 astrocyte-related cytokines.
Keywords: Glial Fibrillary Acidic Protein; cytokiny; S100 Calcium Binding Protein beta Subunit; buněčná diferenciace; Astrocytes; kultivované buňky; Cytokines; Cells, Cultured; indukované pluripotentní kmenové buňky; lidé; astrocyty; S-100 kalcium vázající protein G, podjednotka beta; Aquaporin 4; Humans; gliový fibrilární kyselý protein; akvaporin 4; Cell Differentiation; Induced Pluripotent Stem Cells